A new species of the dance-fly subgenus Xanthempis Bezzi, 1909 of the genus Empis Linnaeus, 1758 (Diptera: Empididae) from the Caucasus - S.Yu. Kustov (Кавказский энтомологический бюллетень, 2011)
This paper describes one new species Empis shamshevi sp. n. of the subgenus Xanthempis Bezzi, 1909 taken from the Caucasian region of Russia (Krasnodar province). Diagnosis. Occiput is almost completely dark, scutum almost entirely black, prescutellar deepening is yellow, scutellum from the front is black while the edges are yellow, postsutural supra-alar bristle is presented. Male: epandrial lamella with long hair-like yellow setae, cercus with a plunging neckline, phallus medium length, relatively thick, arcuately curved, with a long coracoid apex. The changes of key to the Caucasian Xanthempis species [Shamshev, Kustov, 2008] are given. Empis shamshevi sp. n. is most similar to Е. testacea Fabricius, 1805 and E. adriani Chvála, 1996 but it differs from them by almost entirely fused black vittae on the mesonotum, which are slightly separated on its posterior part, and also by the shape of sclerites of male terminalia. In male terminalia the new species resembles Е. zinovjevae Shamshev, 1998, however, this species has single median vitta on the scutum.